2018
DOI: 10.1021/acs.macromol.8b00394
|View full text |Cite
|
Sign up to set email alerts
|

SCFT Study of Diblock Copolymer Melts in Electric Fields: Selective Stabilization of Orthorhombic Fddd Network Phase

Abstract: Using self-consistent field theory (SCFT), we explore the phase behavior of a diblock copolymer (BCP) melt in an applied electric field, with different dielectric constants assigned to each monomer type. The electric field penalizes the interfaces between species domains that are not parallel to the field. Under the present mean-field approximation, lamellar and cylindrical structures reorient to align their interfaces with the electric field, such that these mesophases will have the same electrostatic free en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Given the abiding interest that membrane fabrication has attracted since the seminal works of Bechhold, Kolff and Berk, and Loeb and Sourirajan, we cannot aim for a comprehensive overview but have selected topics related to membrane structure and its nonequilibrium formation processes to highlight common aspects of experiment and theory. Therefore, various important and challenging topics of interest such as, e.g., solvent evaporation from homopolymer mixtures, solvent annealing of copolymer films, directing the orientation of membrane pores by electric fields, polymerization-induced phase-separation (PIPS), or polymerization-induced self-assembly (PISA) have not been covered. Functionalization of membrane pores , and molecular transport on the atomic scale in the membranes that are critical for the operation of membranes are also not addressed in the following.…”
Section: Introductionmentioning
confidence: 99%
“…Given the abiding interest that membrane fabrication has attracted since the seminal works of Bechhold, Kolff and Berk, and Loeb and Sourirajan, we cannot aim for a comprehensive overview but have selected topics related to membrane structure and its nonequilibrium formation processes to highlight common aspects of experiment and theory. Therefore, various important and challenging topics of interest such as, e.g., solvent evaporation from homopolymer mixtures, solvent annealing of copolymer films, directing the orientation of membrane pores by electric fields, polymerization-induced phase-separation (PIPS), or polymerization-induced self-assembly (PISA) have not been covered. Functionalization of membrane pores , and molecular transport on the atomic scale in the membranes that are critical for the operation of membranes are also not addressed in the following.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of using a DC electric field for the orientation of block copolymer lamellae along the field lines was first demonstrated by Amundson et al in the early 90s [33][34][35]. Since then, the electric field effects have been investigated rather intensively Polymers 2021, 13, 3959 2 of 15 experimentally [36][37][38][39][40][41][42][43][44][45][46][47][48], by analytical/numerical theory [49][50][51][52][53][54][55][56][57][58][59][60], and via computer simulations [61][62][63]. It was demonstrated that the electric field has a strong impact on the conditions of order-disorder and order-order transitions in block copolymer melts, solutions, and thin films and can be considered as a precision tool to adjust the morphology of microphase-separated states on a nanometer scale.…”
Section: Introductionmentioning
confidence: 99%
“…BCPs composed of two or more incompatible segments can obtain excellent properties of each segment orthogonally by self-assembling to form various ordered nanostructures, including spheres, hexagonally packed cylinders (HEX), lamellae (LAM), the gyroid network phase (GYR), and the Fddd network phase (O 70 ). However, many properties of BCPs, including the modulus and conductivity, are usually affected by the long-range order of nanostructures. Fortunately, thin-film assembly of BCPs provides a fascinating approach for preparing thin films with long-range ordered nanostructures. In the past decades, various strategies, including magnetic field, electric field, graphoepitaxy, solvent vapor annealing, ,, and supramolecular cooperative motions (SMCMs), , have been explored to control the orientation of nanostructures in BCP thin films.…”
Section: Introductionmentioning
confidence: 99%